Rethinking the living diversity of the Abrocoma cinerea Thomas, 1919 species complex (Rodentia, Abrocomidae) - Teta, Pablo (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
The genus Abrocoma Waterhouse includes eight living species of medium-sized rats with long, soft, and dense fur, large ears, and moderate to short tails. Six of these species are included within the informally called A. cinerea species complex (A. cinerea Thomas, A. budini Thomas, A. famatina Thomas, A. schistacea Thomas, A. vaccarum Thomas, and A. uspallata Braun and Mares). Based both on the study of specimens housed in biological collections and the reinterpretation of previous morphological evidence, I suggest that the current recognized species richness of the genus could be overestimated. Both qualitative and quantitative morphological approaches are consistent with the recognition of no more than two morphotypes within the A. cinerea species complex. However, additional lines of evidence and approaches are needed to disentangle the complex taxonomy of this genus (e.g., phylogenetic analysis of DNA sequences). Until then, I prefer to not make changes in the current classification of Abrocoma, especially taking into account that any taxonomic change could have undesirable consequences in the conservation of these rodents.
Keywords: Hystricognathi; Caviomorpha; Octodontoidea; Chinchilla rat